2011
DOI: 10.1107/s0909049511041240
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for enhancing dispersion of Co3O4nanoparticles in Co/SiO2Fischer–Tropsch synthesis catalyst by adding glycol to impregnating solution: a quick-XAFS study

Abstract: In situ Co K-edge quick-EXAFS (QEXAFS) coupled with temperature-programmed oxidation as well as ex situ XAFS was applied to investigating the mechanism for enhancing the dispersion of Co(3)O(4) nanoparticles in a calcined Co/SiO(2) Fischer-Tropsch synthesis catalyst prepared by adding triethylene glycol (TEG) to a Co(NO(3))(2).6H(2)O impregnating solution. Ex situ Co K-edge XAFS indicated that, regardless of whether the catalysts were prepared with or without using TEG, the hexaaqua Co (II) complex was formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The distinction between the evolution of neighbor structures of Co ions in CNT@Co 3 O 4 and CNT/Co 3 O 4 air electrodes during the electrochemical processes that were further revealed by their Fourier transformed (FT) Co K‐edge EXAFS spectra are shown in Figure b,c, respectively. The first shell of the R‐space for Co EXAFS in Co 3 O 4 is attributed to the CoO coordination, while the 2nd and 3rd shells are attributed to Co(III)Co(III) coordination in octahedral (Oh) symmetry and Co(II)Co(II) coordination in tetrahedral (Td) symmetry, respectively . For CNT@Co 3 O 4 air electrodes, an alternate coordination feature is clearly observed upon discharge compared to the pristine electrode from the shapes of the FT curves, which, nonetheless, nearly fully recovered after charging.…”
Section: Resultsmentioning
confidence: 99%
“…The distinction between the evolution of neighbor structures of Co ions in CNT@Co 3 O 4 and CNT/Co 3 O 4 air electrodes during the electrochemical processes that were further revealed by their Fourier transformed (FT) Co K‐edge EXAFS spectra are shown in Figure b,c, respectively. The first shell of the R‐space for Co EXAFS in Co 3 O 4 is attributed to the CoO coordination, while the 2nd and 3rd shells are attributed to Co(III)Co(III) coordination in octahedral (Oh) symmetry and Co(II)Co(II) coordination in tetrahedral (Td) symmetry, respectively . For CNT@Co 3 O 4 air electrodes, an alternate coordination feature is clearly observed upon discharge compared to the pristine electrode from the shapes of the FT curves, which, nonetheless, nearly fully recovered after charging.…”
Section: Resultsmentioning
confidence: 99%
“…Choy et al [43] utilized EXAFS and XANES at the Co K-edge to demonstrate that a Co-doped-SiO 2 -sol pillared montmorillonite synthesized by interlayer hydrolysis and condensation of TEOS consisted of Co(OH) 2 before calcination but converted to nanosized cobalt oxide covalently bound to the SiO 2 surface after calcination. Koizumi et al [44] utilized quick-EXAFS, temperature programmed oxidation (TPO), and ex situ XAFS to examine how Co 3 O 4 nanoparticles became better dispersed after adding triethylene diglyme (TEG) to a cobalt nitrate solution. The authors observed that small oxide clusters formed with TEG modification and calcination at mild temperatures.…”
Section: Cobalt Catalystsmentioning
confidence: 99%
“…The first section demonstrates how these uncertainties were overcome by coupling XANES and EXAFS spectroscopies to temperature programmed reduction/carburization [32][33][34][35][36][37][38][39][40]. The influence of catalyst preparation [39][40][41][42][43][44] and pretreatment [37,44,45] on activation is also addressed to some extent in this section. The working state of unpromoted catalysts has also been investigated by EXAFS [e.g., 56].…”
Section: Introductionmentioning
confidence: 99%
“…The average coordination number of Cu-Cu among the three catalysts are much smaller than the theoretical value of 8, indicating a lack of Cu neighbors at around 3 Å, which could be explained by the finite size of the CuO particles. As smaller metal oxides particles tend to have more unsaturated M-M coordinated atoms, 48 CuO particles in the CuO/CeO 2 (nr) catalyst which show the smallest average coordination number for Cu-Cu shell should have the smallest average size. The smaller particle size of copper oxide in CuO/CeO 2 (nr) can contribute to explain why this system reduces faster than CuO/CeO 2 (ns) or CuO/CeO 2 (nc) (Fig.…”
Section: Operando Studiesmentioning
confidence: 99%